Exploring Research Trends on Google Classroom: An Analysis from Methodologies to Result-Based Recommendations - Salim, M Agus; Rajabiyah, Nurlaila (LPPM STKIP Kusuma Negara, 2025)
This study explores research trends related to Google Classroom as a digital learning platform, focusing on the analysis of methodologies, research subjects, effectiveness, and resulting recommendations. Using a descriptive meta-analysis approach, this study reviewed 42 articles from Scopus Q1-Q4 indexed journals obtained via Elicit.com. The findings reveal a significant increase in Google Classroom usage during the COVID-19 pandemic, with a dominance of quantitative methodologies (47.6%) emphasizing effectiveness and learning outcomes. University students emerged as the dominant subjects, reflecting the platform’s popularity in higher education. Additionally, Google Classroom has proven effective in supporting independent learning, collaboration, and student engagement. Key recommendations include intensive training, the development of interactive features, and enhanced technological infrastructure to ensure the platform's sustainability and relevance in the future. This study concludes that Google Classroom is a flexible and adaptive learning tool, yet it requires more comprehensive implementation strategies to maximize its potential in digital education.